THE CORRELATION BETWEEN TERPENOID OF SARANG SEMUT (Myrmecodia pendans) WITH mRNA FRUCTOSYLTRANFERASE EXPRESSION OF Streptococcus mutans BIOFILM ATCC 25175 - Satari, Mieke Hemiawati; Chemiawan, Eka; Gartika, Meirina; Rabil, Darul (Odonto : Dental Journal, 2021)
Background: Terpenoid isolate sarang semut (Myrmecodia pendans) is a natural material that has antibacterial power through the destruction of the cell membrane of Streptoccus mutans (S. mutans). Fructosiltransferase (ftf) is one of the extrapolisaccharides produced by S. mutans. The formation of Ftf is governed by the ftf gene. The aim of research was to know the correlation between terpenoid of Sarang semut administration with ftf mRNA expression of S. mutans biofilm ATCC 25175.Method: The study used mixed methods, namely descriptive explorative method to look at the isolation of ftf gene and ftf mRNA expression. This study began with making 1 day biofilm , then given terpenoid isolates of sarang semut and chlorhexidine. Next, isolation of ftf genes and ftf mRNA expression was carried out, then the differences in S. mutans ATCC 25175 mRNA ftf expression in sarang semut and chlorhexidine were given for 1 and 30 minutes using Real-Time PCR. Continued by looking at the relationship of the duration of administration of sarang semut terpenoids to the expression of S. mutans ATCC 25175 mRNA ftf biofilm. Statistical analysis used the t test with p-value <0.05 and Pearson.Results: The results showed that ftf gene with 130 bp length and ftf mRNA expression could be isolated from S. mutans biofilm ATCC 25175 which were given terpenoid isolates from sarang semut. The expression of sarang semut mRNA ftf and chlorhexidine did not have a significant difference for 1 minute (p = 0.0761), whereas in 30 minutes the ant nest had a higher mRNA expression (p = 0.0186). There is a relationship between the duration of administration of terpenoid isolates of sarang semut with S. mutans ATCC 25175 mRNA ftf expression (r2 = 0.614), with a medium correlation coefficient.Conclusion: The conclusion of the study were that sarang semut terpenoid had the same effect as chlorhexidine for 1 minute on S. mutans biofilms, whereas at 30 minutes it was different. There is a relationship between terpenoids of sarang semut isolates and S. mutans biofilm ATCC 25175 mRNA expression.